Genome-wide identification and expression analysis of ZF-HD family in sunflower (Helianthus annuus L.) under drought and salt stresses - Kangping Zhang; Ruqian Yan; Xiaoqing Feng; Jingjing Zhang; Yuanyuan Jiang; Lin Li; Jianzhong Guo; Xianping Zhang (BMC Plant Biology)
Abstract Background Sunflower (Helianthus annuus L.) is widely cultured in globally tropical and subtropical regions, with better resistance to various abiotic stresses as a model crop. Despite the fact that zinc finger-homeodomain (ZF-HD) genes play an important role in responding to plant growth, development and stress resistance across the multiple species, the evolutionary history and abiotic function of the ZF-HD gene family in sunflower remain largely unexplored. Results In this study, we identified 15 HaZF-HD genes (designated as HaZF1–HaZF15) in the sunflower genome, and they were divided into MIF and ZHD subfamilies. The proteins from the same group were similar in conserved motifs and domains, such as motif 1 and motif 3, constituting the ZF domain, were almost existed in 15 HaZF-HD proteins. Motif 2 (HD domain) was specifically presented in the ZHD subfamily. Collinearity analysis revealed that 5 pairs of genes with fragment duplication contributed to the expansion of HaZF-HD gene family. The analysis of cis-acting element demonstrated that the response elements related the hormone response and abiotic/biotic stress were the most prevalent, followed by plant growth and development elements. In the tissue expression profile, HaZF-HD gene family had the highest expression in leaves and floral organs. Additionally, RNA-seq and RT-qPCR analysis revealed HaZF3 responded positively in the initial stage of drought stress, whereas a prompt and significant decrease of relative expression value in response to salt stress was showed in HaZF6 and HaZF9. Conclusions Overall, this study enhances our comprehension of the function of ZF-HD genes in positive regulation of responsiveness to abiotic stress and provide key candidate genes for sunflower stress resistance breeding.